The impact of work environment on caring behavior among Chinese hospice nurses: the chain mediating effect of psychological capital and empathy - Wang, Tiantian; Li, Yunrong; Chen, Jie; Meng, Aifeng; Wang, Yeping; Zhang, Liuliu; Wu, Bing; Yang, Bo; Zhao, Yun (Frontiers in Psychology, 2024)
The caring behavior of hospice nurses toward patients positively impacts their professional careers and significantly improves the quality of hospice services. A positive and supportive work environment may protect nurses against negative emotions that may affect the humanistic care they provide, and their job satisfaction. This study aimed to explore the impact of the nursing work environment on caring behavior. We also investigated the chain mediating effect of psychological capital and empathy on this relationship among Chinese hospice nurses.The Practice Environment Scale (PES), the Psychological Capital Questionnaire (PCQ), the Empathy Ability Scale for Hospice Nurses, and the Caring Behaviors Inventory (CBI) were used to survey 393 Chinese hospice nurses. SPSS 27.0 and Mplus 8.0 were used for statistical processing to analyze the mediating effects.The nursing work environment positively predicted caring behavior. Furthermore, it was found that psychological capital and empathy jointly mediate the relationship between the nursing work environment and caring behavior.This study reveals how the nursing work environment affects the caring behavior of hospice nurses. Hospital managers need to provide hospice nurses with a favorable working environment from the perspective of positive psychology, continuously monitor their psychological state, improve their caring behavior, and provide references for developing intervention plans to promote the caring behavior of hospice nurses in the future.